2020
DOI: 10.12659/msm.926807
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Chemokines in the Paraventricular Nucleus of the Hypothalamus in Rats with Stress-Induced Hypertension

Abstract: Background The neuroinflammation of paraventricular nucleus (PVN) of the hypothalamus has been implicated in the development of hypertension. The promoted invasion of peripheral immune cells into PVN may be attributed to the upregulation of chemokines, then exacerbating neuroinflammation. We studied the expressions of chemokines, activation of microglial cells, and inflammatory mediators in PVN of rats with stress-induced hypertension (SIH). Material/Methods SIH was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Previously, we demonstrated that different types of acute exercise, such as swimming and treadmill running, increased the Il6 mRNA levels in the hypothalamus of mice ( 14 ) Similarly, stress protocols up-regulated Il6 mRNA expression in rat hypothalamus ( 38 , 51 ). In addition, a high capacity of hypothalamic microglial cells of mice to produce IL6 under several acute or chronic circumstances has been demonstrated ( 52 ).…”
Section: Discussionmentioning
confidence: 90%
“…Previously, we demonstrated that different types of acute exercise, such as swimming and treadmill running, increased the Il6 mRNA levels in the hypothalamus of mice ( 14 ) Similarly, stress protocols up-regulated Il6 mRNA expression in rat hypothalamus ( 38 , 51 ). In addition, a high capacity of hypothalamic microglial cells of mice to produce IL6 under several acute or chronic circumstances has been demonstrated ( 52 ).…”
Section: Discussionmentioning
confidence: 90%
“…The PVN in the hypothalamus is a crucial BP regulation center [205], controlling other important nuclei and their circuits in the CNS, especially the rostroventrolateral medulla and nucleus tractus solitarius in the hindbrain, which is necessary for BP control [206][207][208]. Several studies have reported elevated proinflammatory cytokines expression in the PVN of animal hypertension models [209][210][211][212][213]. Further, the microinjection of inflammatory cytokines, such as TNF-α or IL-1β, into the PVN results in increased sympathetic outflow and increased afferent cardiac sympathetic reflex associated with an elevated BP [214].…”
Section: Hypertension and Hypothalamic Inflammationmentioning
confidence: 99%
“…Leukocyte infiltration into the vessel wall is a key step in the development of hypertension. Alterations in CXCL7 can lead to a change in the inflammatory state in stress hypertension ( Wu et al, 2020 ). Neutrophils play an important role in the development of delayed cerebral vasospasm (DCV) after aneurysmal subarachnoid hemorrhage.…”
Section: The Biological Characteristics Of Cxcl7mentioning
confidence: 99%